Improving Road and Sidewalk Accessibility for Persons with Disabilities: Infrastructure Challenges and Legal Compliance in Indonesia - Muhammad Jabir Muhammadiah; Ahmad Selao (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Research to address significant challenges related to public infrastructure accessibility, especially for disabilities, regarding regulations that govern accessibility, the implementation in the field is still far from adequate. The research aims to evaluate the condition of public infrastructure, identify accessibility barriers for disabilities, and provide recommendations for future improvements. A mixed-methods approach, with participatory research methodology, provides significant contributions to disability and urban planning. Probability sampling method, with 150 respondents, physical, intellectual, and sensory disabilities, as well as experiences and challenges of accessibility. Data analysis, qualitative and quantitative methods, thematic analysis to analyze qualitative data about PWD experiences, descriptive and inferential statistical analysis for quantitative data. The findings indicate that road and sidewalk infrastructure is inadequate, with uneven surfaces, a lack of supporting facilities such as ramps, and unclear signage. Persons with disabilities are isolated from participating in public spaces, highlighting the gap between regulations and their implementation on the ground. The findings emphasize the integration of universal design in future infrastructure planning. Involving disabilities in planning results in more inclusive and effective solutions. Improving training and awareness for urban planners, along with regular monitoring of public infrastructure, ensures compliance with accessibility standards, moving towards a Smart Disability City (SDC)